Implementasi Program Kota Tanpa Kumuh (KOTAKU) sebagai Inovasi dalam Penanggulangan Kemiskinan Masyarakat di Kecamatan Muntok Kabupaten Bangka Barat Tahun 2016-2020 - Belasari Belasari; Bustami Rahman; Ranto Ranto (Inovbook, 2022)
ABSTRACT Belasari,Evaluation of the City Without Slums (KOTAKU) Program in Reducing Community Poverty in Muntok District, West Bangka Regency 2016-2020 (Supervised by Bustami Rahman and Ranto) The City Without Slums Program (KOTAKU) is a program in handling slum areas both in villages and in cities in poverty alleviation. This program has the aim of increasing public access to infrastructure and basic services to improve livable areas. The number of slum areas in both urban and rural areas makes the government more observant in dealing with them. Like population growth, it can lead to the emergence of slum areas which are often seen as a problem for every region. To reduce these problems, one of the government's programs is the City Without Slums Program (KOTAKU). The purpose of this study was to determine the implementation process and the achievements that have been achieved by the City Without Slums Program (KOTAKU). The theory used in this research is the public policy theory of Charles O. Jones to analyze the evaluation of the City Without Slums Program (KOTAKU). According to Charles O. Jones, the evaluation of the program consists of three parts, namely political evaluation, organizational evaluation, and tangible evaluation. The method used in this research is descriptive qualitative method, the primary data source is interviews with 11 informants. The informants were from the head in charge of this program, the village head and the Lurah, the head of the LKM from the Tanjung and Air Putih villages as well as the last 3 people from the Tanjung village and 3 from the Air Putih village. The results of this study indicate that the evaluation in the two regions was quite successful. Judging from the process of implementing this program, to be precise in the two regions, there have been changes from slums to less slums. Furthermore, for the achievement of the two regions, infrastructure development has been built so that the surrounding community is helped by the Cities Without Slums (KOTAKU) Program, although it has not been fully realized from some of these aspects. With this, the evaluation of the City Without Slums Program (KOTAKU) in the two regions was quite successful. Keywords: Evaluation, City Without Slums Program (KOTAKU), Poverty Alleviation